KARAKTERISTIK PASIEN KANKER SERVIKS DI RSUP SANGLAH DENPASAR PERIODE 1 JANUARI – 31 DESEMBER 2017 - Ni Putu Pramana Saras Utami; I Nyoman Bayu Mahendra; Endang Sri Widiyanti; Jaqueline Sudiman (E-Jurnal Medika Udayana, 2020)
Cervical cancer is one of the most serious malignancies because of its high incidence and transmission rate, which is around 270.000 female mortality cases occured in 2015 because of cervical cancer and 85% occured in developing countries such as Indonesia. The aim is to knowing the characteristics of cervical cancer patient at Sanglah Denpasar General Hospital during period 1st January – 31st December 2017. This research is descriptive and cross sectional. Sampling technique is total sampling where the research data comes from secondary data which is medical record of cervical cancer patient at Sanglah Denpasar General Hospital during period 1st January – 31st December 2017. The highest incidence of cervical cancer was found in group 41-50 years old as many as 23 people (32.9%), had the highest education level at elementary school as many as 34 people (48.6%), worked as housewife as many as 32 people (45.7%), majority did not have history of smoking as many as 68 people (97.1%) and did not have history of using oral contraceptive as many as 64 people (91.4%), had the age of first marriage in group 20-30 years old as many as 33 people (47.1%), have been married once as many as 67 people (95.7%), have three parity as many as 23 people (32.9%), had squamous cell carcinoma non keratinizing histopathology biopsy type as many as 47 people (67.1%), and first diagnosed with cervical cancer in stadium III B as many as 31 people (44.3%). Keywords : cervical cancer, characteristic, age, education, occupation, smoking history, oral contraceptive use history, age of first marriage, number of marriage, number of parity, histopathology biopsy result, clinical stadium